Workshop Strategi Belajar Bahasa Inggris Bagi Mahasiswa di Universitas Islam Riau - Andi Idayani; Betty Sailun (Pusat Riset dan Inovasi Nasional, 2023)
The implementation of this service is motivated by the importance of mastering English in this day. Based on the facts in the field that the world of work demands English proficiency for applicants from all educational backgrounds. This is of course a concern for educators how to motivate students to like English from an early age. Therefore, the purpose of this service is to provide information about effective English learning strategies for Riau Islamic University students. The service team chose FKIP students as service participants on the grounds that they could increase their knowledge so they could master English well. It is hoped that FKIP graduates will be able to use their English language skills to get wider job opportunities and open up opportunities for them to be able to teach Indonesian to foreign speakers abroad. This activity was carried out online using a Google meeting which was attended by 29 semester 6 students. The service team divided the activities into 2 sessions, namely the first session was a presentation on English learning strategies and continued with a second session on motivating FKIP graduates with information on the benefits of mastering English for the world Work. The results of the dedication that has been carried out received a positive response from all participants. All service participants said that they gained additional knowledge about English learning strategies, were motivated to master English and increased their knowledge of mastering English vocabulary. So it can be concluded that the service mentioned above has provided benefits and knowledge about English, especially regarding English learning strategies for UIR FKIP students.